In Vitro and In Vivo Studies of the Trypanocidal Activity of a Diarylthiophene Diamidine against Trypanosoma cruzi - da Silva, Cristiane França (American Society for Microbiology (ASM), 2008)
Aromatic diamidines are DNA minor groove-binding ligands that display excellent antimicrobial activity against fungi, bacteria, and protozoa. Due to the currently unsatisfactory chemotherapy for Chagas’ disease and in view of our previous reports regarding the effect of diamidines and analogues against both in vitro and in vivo Trypanosoma cruzi infection, this study evaluated the effects of a diarylthiophene diamidine (DB1362) against both amastigotes and bloodstream trypomastigotes of T. cruzi, the etiological agent of Chagas’ disease. The data show the potent in vitro activity of DB1362 against both parasite forms that are relevant for mammalian infection at doses which do not exhibit cytotoxicity. Ultrastructural analysis and flow cytometry studies show striking alterations in the nuclei and mitochondria of the bloodstream parasites. In vivo studies were performed at two different drug concentrations (25 and 50 mg/kg/day) using a 2-day or a 10-day regimen. The best results were obtained when acutely infected mice were treated with two doses at the lower concentration, resulting in 100% survival, compared to the infected and untreated mice. Although it did not display higher efficacy than benznidazole, DB1362 reduced both cardiac parasitism and inflammation, and in addition, it protected against the cardiac alterations (determined by measurements) common in T. cruzi infection. These results support further investigation of diamidines and related compounds as potential agents against Chagas’ disease.